In Situ Hybrid Aluminum Matrix Composites: A Review of Phase Transformations and Mechanical Aspects. Issue 7 (15th April 2019) - Azarniya, Amir; Azarniya, Abolfazl; Abdollah‐zadeh, Amir; Madaah Hosseini, Hamid Reza; Ramakrishna, Seeram
Abstract : The growing industrial needs for the development of strong load‐bearing materials by powder metallurgy and casting technologies has led to recent progress in the synthesis of in situ hybrid aluminium matrix composites (AMCs). Unlike their conventional counterparts, this class of engineering materials and their physicomechanical properties are sparsely investigated with no satisfactorily systematic approach and are not reviewed up to now. This is why providing an overview summarizing the formation mechanisms of in situ phases and mechanical properties of hybrid AMCs can systematically guide the research path in this field. The present review strives to categorize hybrid AMCs based on their dominant in situ formed reinforcements and draw a comparison between different fabrication methods and used starting materials. Finally, the present challenges and potential solutions are addressed both from scientific and technological aspects. Abstract : The present review paper adopts a systematic approach to categorize in situ hybrid aluminium matrix composites based on their dominant in situ formed reinforcements including Al3 Ti, Al2 O3, and TiB2 . It reviews different fabrication methods, in situ phase formation mechanisms, mechanical properties of the composites, as well as the present challenges and potential solutions from both scientific and technological aspects.